Phân tích đa thức thành nhân tử `A = a(a + 2b)^3 – b(2a + b)^3`

Question

Phân tích đa thức thành nhân tử
`A = a(a + 2b)^3 – b(2a + b)^3`

in progress 0
Anna 2 tháng 2021-07-24T19:08:38+00:00 2 Answers 10 views 0

Answers ( )

    0
    2021-07-24T19:10:07+00:00

    Đáp án:

     

    Giải thích các bước giải:

     A=a.(a +2b)³ -b.(2a +b)³

       =a.(a³ +6a²b +12ab² +8b³) -b.( 8a³ +12a²b +6ab² +b³)

       =$a^{4}$  +6a³b +12a²b² +8ab³ -8a³b -12a²b² -6ab³ -$b^{4}$ 

       =$a^{4}$ -$b^{4}$  -2a³b +2ab³

      =(a²-b²).(a² +b²)  -2ab.(a² -b²)

      =(a² -b²).( a² -2ab +b²)

      =(a-b).(a +b).(a-b)²

      =(a-b)³ .(a+b)

    0
    2021-07-24T19:10:21+00:00

    Đáp án:

    Ta có : 

    `A = a(a + 2b)^3 – b(2a + b)^3`

    `= a[(a + b) + b]^3 – b[(a + b) + a]^3`

    `= a.[(a + b)^3 + 3(a + b)^2b + 3(a + b)b^2 + b^3] – b[(a + b)^3 + 3(a + b)^2a + 3(a + b)a^2 + a^3]`

    ` = a(a + b)^3 + 3ab(a + b)^2 + 3a(a + b)b^2 + ab^3 – b(a + b)^3 – 3ab(a + b)^2 – 3b(a + b)a^2 – ba^3`

    `= a(a + b)^3 + 3a(a + b)b^2 + ab^3 – b(a + b)^3 – 3b(a + b)a^2 – ba^3`

    `= [a(a + b)^3 – b(a + b)^3] + [3a(a + b)b^2 – 3b(a + b)a^2] + [ab^3 – ba^3]`

    `= (a + b)^3(a – b) + 3ab(a + b)(b – a) + ab(b^2 – a^2)`

    `= (-a^3 – 3a^2b – 3ab^2 – b^3)(b – a) + 3ab(a + b)(b – a) + ab(b + a)(b – a)`

    `= (b – a)[-a^3 – 3a^2b – 3ab^2 – b^3 + 3ab(a + b) + ab(b + a)]`

    `= (b – a)(-a^3 – 3a^2b – 3ab^2 – b^3 + 3a^2b + 3ab^2 + ab^2 + a^2b]`

    `= (b – a)(-a^3 – b^3 + ab^2 + a^2b)`

    `= (a – b)(a^3 + b^3 – ab^2 – a^2b)`

    `= (a – b)[(a^3 – a^2b) – (ab^2 – b^3)]`

    `= (a – b)[a^2(a – b) – b^2(a – b)]`

    `= (a – b)(a – b)(a^2 – b^2)`

    `= (a – b)(a – b)(a – b)(a + b)`

    `= (a – b)^3(a + b)`

    Giải thích các bước giải:

     

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )